Assessing EGFR‐mutated NSCLC with bone metastasis: Clinical features and optimal treatment strategy - Chen, Wei‐Chun; Cheng, Wen‐Chien; Chen, Chieh‐Lung; Liao, Wei‐Chih; Chen, Chia‐Hung; Chen, Hung‐Jen; Tu, Chih‐Yen; Lin, Chi‐Chen; Hsia, Te‐Chun (Cancer medicine (Malden, MA), 2024)
Background This study aimed to examine the clinical characteristics of bone metastasis (BoM) in patients with non‐small cell lung cancer (NSCLC) who have an epidermal growth factor receptor (EGFR) mutation and to identify the most effective treatment strategy using EGFR–tyrosine kinase inhibitors (TKIs). Methods The study included patients with stage IV EGFR‐mutated NSCLC who were receiving first‐line treatment with EGFR–TKIs between January 2014 and December 2020. These patients were divided into two groups based on the presence or absence of BoM at the time of initial diagnosis. The BoM group was further subdivided based on whether they received denosumab or not. Results The final analysis included 247 patients. Those with BoM at initial diagnosis had shorter progression‐free survival (12.6 vs. 10.5 months, p = 0.002) and overall survival (OS) (49.7 vs. 30.9 months, p = 0.002) compared to those without BoM. There was a difference in the location of metastatic sites between the two groups, with a higher incidence of extrathoracic metastasis in the BoM group (p < 0.001). The incidence of T790M was higher in patients with BoM than in those without (47.4% vs. 33.9%, p = 0.042). Multivariate Cox regression analysis revealed that sequential osimertinib treatment and the addition of antiangiogenic therapy (AAT) and denosumab therapy improved OS in patients with BoM. Conclusions The presence of BoM is a negative prognostic factor for NSCLC patients with an EGFR mutation, possibly due to the presence of extrathoracic metastases. However, adding AAT and denosumab, along with sequential osimertinib, to the treatment regimen for patients with BoM can improve survival outcomes.